High-Quality Specification of Self-Adaptive Software Systems - Luckey, Markus; Engels, Gregor (Proceeding of the 8th international symposium on Software engineering for adaptive and self-managing systems)

Decision Support via Automated Metric Comparison for the Palladio-based Performance Blame Analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 4th ACM/SPEC International Conference on Performance Engineering (ICPE 2013), Prague (Czech Republic))

Performance Analysis of Self-Adaptive Systems for Requirements Validation at Design-Time - Becker, Matthias; Luckey, Markus; Becker, Steffen (Ninth International ACM Sigsoft Conference on the Quality of Software Architectures)

Integrating Coverage Analysis into Test-driven Development of Model Transformations - Küster, Jochen; Kovács, Dániel; Bauer, Eduard; Gerth, Christian

Automated Service Discovery and Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor

Konzeption modellbasierter Benutzungsschnittstellen für verteilte Selbstbedienungssysteme - Yigitbas, Enes; Gerth, Christian; Sauer, Stefan (Informatik 2013, 43. Jahrestagung der Gesellschaft für Informatik e.V. (GI), Informatik angepasst an Mensch, Organisation und Umwelt, 16.-20. September 2013, Koblenz, Deutschland)

A Taxonomy-Based Approach towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard (Distributed, Ambient, and Pervasive Interactions)

Towards a Holistic Tool for the Selection and Validation of Usability Method Sets Supporting Human-Centered Design - Fischer, Holger Gerhard; Strenge, Benjamin; Nebe, Karsten (Design, User Experience, and Usability. Design Philosophy, Methods, and Tools)

Do You Speak Usability? - Aktueller Stand des Glossars und des Curriculums für den Certified Professional for Usability and User Experience (CPUX) der German UPA - Fischer, Holger Gerhard; Geis, Thomas; Molich, Rolf; Kluge, Oliver; Heimgärtner, Rüdiger; Hunkirchen, Peter (Jahresband Usability Professionals)

Service Matching under Consideration of Explicitly Specified Service Variants - Platenius, Marie Christin; von Detten, Markus; Gerth, Christian; Schäfer, Wilhelm; Engels, Gregor (IEEE 20th International Conference on Web Services (ICWS 2013))
One of the main ideas of Service-Oriented Computing (SOC) is the delivery of flexibly composable services provided on world-wide markets. For a successful service discovery,service requests have to be matched with the available service offers. However, in a situation in which no service that completely matches the request can be discovered, the customer may tolerate slight discrepancies between request and offer. Some existing fuzzy matching approaches are able to detectsuch service variants, but they do not allow to explicitly specify which parts of a request are not mandatory. In this paper, we improve an existing service matching approach based onVisual Contracts leveraging our preliminary work of design pattern detection. Thereby, we support explicit specifications of service variants and realize gradual matching results that can be ranked in order to discover the service offer that matches a customer’s request best.

Software Engineering for Self-Adaptive Systems: A Second Research Roadmap - de Lemos, Rogrio; Giese, Holger; A. Müller, Hausi; Shaw, Mary; Andersson, Jesper; Litoiu, Marin; Schmerl, Bradley; Tamura, Gabriel; M. Villegas, Norha; Vogel, Thomas; Weyns, Danny; Baresi, Luciano; et al. (Software Engineering for Self-Adaptive Systems II)

Leichtgewichtige Traceability im agilen Entwicklungsprozess am Beispiel von Scrum - Bouillon, Elke; Güldali, Baris; Herrmann, Andrea; Keuler, Thorsten; Moldt, Daniel; Riebisch, Matthias (Softwaretechnik-Trends)

Testen bei Migrationsprojekten - Grieger, Marvin; Güldali, Baris; Sauer, Stefan; Mlynarski, Michael (OBJEKTspektrum (Online Themenspecials))

Maßgeschneidert und werkzeugunterstützt Entwickeln angepasster Requirements Engineering-Methoden - Fazal-Baqaie, Masud; Güldali, Baris; Luckey, Markus; Sauer, Stefan; Spijkerman, Michael (OBJEKTspektrum (Online Themenspecials))

Editorial - Engels, Gregor; Luckey, Markus (Computer Science - Research and Development)

Informationstechnik spart Ressourcen - Engels, Gregor; Gerth, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Müller, Wolfgang; Sauer, Stefan (Forschungsforum Paderborn)

Detection and Resolution of Conflicting Change Operations in Version Management of Process Models - Gerth, Christian; Küster, Jochen; Luckey, Markus; Engels, Gregor (Software and Systems Modeling)

Wirtschaftlichkeitsberechnung für MBT: Wann sich modellbasiertes Testen lohnt - Faragó, David; Törsel, Arne-Michael; Mlynarski, Michael; Weißleder, Stephan; Güldali, Baris; Brandes, Christian (OBJEKTspektrum)
Modellbasiertes Testen verspricht potenziell eine höhere Effizienz und Effektivität im Testprozess. Ob im eigenen Kontext der Einsatz wirtschaftlich ist, ist jedoch häufig unklar. Dieser Beitrag analysiert systematisch Kosten- und Nutzenfaktoren und stellt ein Verfahren zur Abschätzung der Wirtschaftlichkeit des modellbasierten Testens vor. Anhand eines Beispiels wird der Ablauf veranschaulicht.

Object-oriented Modeling of Multimedia Applications - Engels, Gregor; Sauer, Stefan (Handbook of Software Engineering and Knowledge Engineering)

Quality Assurance with Dynamic Meta Modeling - Soltenborn, Christian
Dynamic Meta Modeling (DMM) is a semantics specification technique targeted at MOF-based modeling languages, where a language's behavior is defined by means of graphical operational rules which change runtime models. The DMM approach has first been suggested by Engels et al. in 2000; Hausmann has then defined the DMM language on a conceptual level within his PhD thesis in 2006. Consequently, the next step was to bring the existing DMM concepts alive, and then to apply them to different modeling languages, making use of the lessons learned to improve the DMM concepts as well as the DMM tooling. The result of this process is the DMM++ method, which is presented within this thesis. Our contributions are three-fold: First, and according to our experiences with the DMM language, we have introduced new concepts such as refinement by means of rule overriding, and we have strengthened existing concepts such as the dealing with universally quantified structures or attributes. Second, we have developed a test-driven process for semantics specification: A set of test models is created, and their expected behavior is fixed. Then, the DMM rules are created incrementally, finally resulting in a DMM ruleset realizing at least the expected behavior of the test models. Additionally, we have defined a set of coverage criteria for DMM rulesets which allow to measure the quality of a set of test models. Third, we have shown how functional as well as non-functional requirements can be formulated against models and their DMM specifications. The former is achieved by providing a visual language for formulating temporal logic properties, which are then verified with model checking techniques, and by allowing for visual debugging of models failing a requirement. For the latter, the modeler can add performance information to models and analyze their performance properties, e.g. average throughput.

Business Process Models - Change Management - Gerth, Christian
Driven by the need for a closer alignment of business and IT requirements, the role of business process models in the development of enterprise software systems has increased continuously. Similar to other software artifacts, process models are developed and refined in team environments by several stakeholders, resulting in different versions. These versions need to be merged in order to obtain an integrated process model. Existing solutions to this basic problem in the field of software configuration management are mainly limited to textual documents, e.g., source code. This monograph presents a generally applicable framework for process model change management, which provides easy-to-use comparison and merging capabilities for the integration of different process model versions. The framework supports popular modeling languages such as BPMN, BPEL, or UML Activity Diagrams. Differences between process models are represented in terms of intuitive, high-level change operations. Equipped with a sophisticated analysis of dependencies and a semantic-aware computation of conflicts between differences, the framework constitutes a comprehensive and practically usable solution for process model change management in the model-driven development of enterprise software systems.

Ein pragmatischer Ansatz zur Entwicklung situationsgerechter Entwicklungsmethoden - Spijkerman, Michael (Software Engineering 2013 - Workshopband (inkl. Doktorandensymposium) SE 2013 (to appear))

Kaos4SOA - Extending KAOS Models with Temporal and Logical Dependencies - Nagel , Benjamin; Gerth , Christian; Post, Jennifer; Engels, Gregor (Proceedings of the CAiSE'13 Forum at the 25th International Conference on Advanced Information Systems Engineering (CAiSE'13))

CVSM 2013 Challenge: Recognizing High-level Edit Operations in Evolving Models. - Kehrer , Timo; Gerth, Christian (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'13))

Wiederverwendbarkeit von Migrationswissen durch Techniken der modellgetriebenen Softwareentwicklung - Grieger , Marvin; Sauer, Stefan (Software Engineering 2013 Workshopband)

Goal-driven Composition of Business Process Models - Nagel , Benjamin; Gerth , Christian; Engels, Gregor (Proceedings of the 9th Workshop on Engineering Service-Oriented Applications (WESOA 2013) (accepted for application))

Assembly-based Method Engineering with Method Patterns - Fazal-Baqaie , Masud; Luckey , Markus; Engels, Gregor (Software Engineering 2013 Workshopband)

On-The-Fly Computing -- Das Entwicklungs- und Betriebsparadigma fürSoftwaresysteme der Zukunft - Engels, Gregor (Proceedings of the Multikonferenz Sofware Engineering 2013 (SE 2013))
Alle Domänen und Branchen der heutigen Wirtschaft sind auf eine effiziente und effektive Entwicklung von benötigten Softwaresystemen angewiesen. Das 40 Jahre alte Prinzip der Beschaffung von Softwaresystemen durch den Einkauf von teuren, relativ unflexiblen Standardlösungen beziehungsweise der noch teureren Erstellung durch Softwarehäuser oder eigene Softwareabteilungen muss deshalb in Frage gestellt werden. Mit dem Einsatz von Cloud Computing-Techniken wird es möglich, Softwaresysteme und die für den Betrieb benötigten Ressourcen nur bei Bedarf und nur in der benötigten Form einzukaufen. Mit dem Ansatz der service-orientierten Architekturen stehen Methoden zur Verfügung, Software zumindest unternehmensintern flexibel zusammenzustellen. Diese ersten Ansätze für eine neue Art der Entwicklung und des Betriebs von Softwaresystemen bilden den Ausgangspunkt für die Forschungen in dem seit 2011 laufenden DFG Sonderforschungsbereich (SFB) 901 „On-The-Fly Computing“ an der Universität Paderborn. Die Vision des On-The-Fly Computing ist, dass die Softwaresysteme der Zukunft aus individuell und automatisch konfigurierten und zur Ausführung gebrachten Softwarebausteinen bestehen, die auf Märkten frei gehandelt werden und flexibel kombinierbar sind. Um zu erforschen, in wie weit diese Vision realisierbar ist, werden Konzepte, Methoden und Techniken entwickelt, die eine weitestgehend automatische Konfiguration, Ausführung und Adaption von Softwaresystemen aus auf weltweiten Märkten verfügbaren Services ermöglichen. Um diese Ziele zu erreichen, arbeiten an der Universität Paderborn Informatiker aus unterschiedlichen Disziplinen wie Softwaretechnik, Algorithmik, Rechnernetze, Systementwurf, Sicherheit und Kryptographie mit Wirtschaftswissenschaftlern zusammen, die ihre spezifische Expertise einbringen, mit der die Organisation und Weiterentwicklung des Marktes vorangetrieben werden kann.

Business Process Models - Change Management - Gerth, Christian
In recent years, the role of process models in the development of enterprise software systems has increased continuously. Today, process models are used at different levels in the development process. For instance, in Service-Oriented Architectures (SOA), high-level business process models become input for the development of IT systems, and in running IT systems executable process models describe choreographies of Web Services. A key driver behind this development is the necessity for a closer alignment of business and IT requirements, to reduce the reaction times in software development to frequent changes in competitive markets.Typically in these scenarios, process models are developed, maintained, and transformed in a team environment by several stakeholders that are often from different business units, resulting in different versions. To obtain integrated process models comprising the changes applied to different versions, the versions need to be consolidated by means of model change management. Change management for process models can be compared to widely used concurrent versioning systems (CVS) and consists of the following major activities: matching of process models, detection of differences, computation of dependencies and conflicts between differences, and merging of process models.Although in general model-driven development (MDD) is accepted as a well-established development approach, there are still some shortcomings that let developers decide against MDD and for more traditional development paradigms. These shortcomings comprise a lack of fully integrated and fully featured development environments for MDD, such as a comprehensive support for model change management.In this thesis, we present a framework for process model change management. The framework is based on an intermediate representation for process models that serves as an abstraction of specific process modeling languages and focuses on common syntactic and semantic core concepts for the modeling of workflow in process models. Based on the intermediate representation, we match process models in versioning scenarios and compute differences between process models generically. Further, we consider the analysis of dependencies between differences and show how conflicts between differences can be computed by taking into account the semantics of the modeling language.As proof-of concept, we have implemented major parts of this framework in terms of a prototype. The detection of differences and dependencies contributed also to the Compare & Merge framework for the IBM WebSphere Business Modeler V 7.0 [1] (WBM), which was released as a product in fall 2009.

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))
In the service-oriented computing domain, the number of available software services steadily increased in recent years, favored by the rise of cloud computing with its attached delivery models like Software-as-a-Service (SaaS). To fully leverage the opportunities provided by these services for developing highly flexible and aligned SOA, integration of new services as well as the substitution of existing services must be simplified. As a consequence, approaches for automated and accurate service discovery and composition are needed. In this paper, we propose an automatic service composition approach as an extension to our earlier work on automatic service discovery. To ensure accurate results, it matches service requests and available offers based on their structural as well as behavioral aspects. Afterwards, possible service compositions are determined by composing service protocols through a composition strategy based on labeled transition systems.

A Survey of Fuzzy Service Matching Approaches in the Context of On-The-Fly Computing - Platenius, Marie; von Detten, Markus; Becker, Steffen; Schäfer, Wilhelm; Engels, Gregor (Proceedings of the 16th International ACM Sigsoft Symposium on Component-Based Software Engineering)
In the last decades, development turned from monolithic software products towards more flexible software components that can be provided on world-wide markets in form of services. Customers request such services or compositions of several services. However, in many cases, discovering the best services to address a given request is a tough challenge and requires expressive, gradual matching results, considering different aspects of a service description, e.g., inputs/ouputs, protocols, or quality properties. Furthermore,in situations in which no service exactly satifies the request, approximate matching which can deal with a certain amount of fuzziness becomes necessary. There is a wealth of service matching approaches, but it is not clear whether there is a comprehensive, fuzzy matching approach which addresses all these challenges. Although there are a few service matchingsurveys, none of them is able to answer this question. In this paper, we perform a systematic literature survey of 35 (outof 504) service matching approaches which consider fuzzy matching. Based on this survey, we propose a classication,discuss how different matching approaches can be combined into a comprehensive matching method, and identify future research challenges.

Relational semantics for full linear logic - Coumans, Dion; Gehrke, Mai; van Rooijen, Lorijn (Journal of Applied Logic)

Separating Regular Languages by Locally Testable and Locally Threshold Testable Languages - Place, Thomas; van Rooijen, Lorijn; Zeitoun, Marc (Annual Conference on Foundations of Software Technology and Theoretical Computer Science, (FSTTCS) 2013, December 12-14, 2013, Guwahati, India)

Separating Regular Languages by Piecewise Testable and Unambiguous Languages - Place, Thomas; van Rooijen, Lorijn; Zeitoun, Marc (Mathematical Foundations of Computer Science 2013 - 38th International Symposium, (MFCS) 2013, Klosterneuburg, Austria, August 26-30, 2013)

Graph Transformation - 6th International Conference, ICGT 2012, Bremen, Germany, September 24-29, 2012, Proceedings

Model-driven Performance Engineering of Self-Adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen (Proceedings of the International Conference on Quality of Software Architecture)

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MODELS'12))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers. However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Towards an Automatic Service Discovery for UML-based Rich Service Descriptions - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the ACM/IEEE 15th International Conference on Model Driven Engineering Languages and Systems (MoDELS))
Service-oriented computing (SOC) promises to solve many issues in the area of distributed software development, e.g. the realization of the loose coupling pattern in practice through service discovery and invocation. For this purpose, service descriptions must comprise structural as well as behavioral information of the services otherwise an accurate service discovery is not possible. We addressed this issue in our previous paper and proposed a UML-based rich service description language (RSDL) providing comprehensive notations to specify service requests and offers.However, the automatic matching of service requests and offers specified in a RSDL for the purpose of service discovery is a complex task, due to multifaceted heterogeneity of the service partners. This heterogeneity includes the use of different underlying ontologies or different levels of granularity in the specification itself resulting in complex mappings between service requests and offers. In this paper, we present an automatic matching mechanism for service requests and offers specified in a RSDL that overcomes the underlying heterogeneity of the service partners.

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))
In software markets of the future, customer-specific software will be developed on demand from distributed software and hardware services available on world-wide markets. Having a request, services have to be automatically discovered and composed. For that purpose, services have to be matched based on their specifications. For the accurate matching, services have to be described comprehensively that requires the integration of different domain-specific languages (DSLs) used for functional, non-functional, and infrastructural properties. Since different service providers use plenty of language dialects to model the same service property, their integration is needed for the matching. In this paper, we propose a framework for integration of DSLs. It is based on a parameterized abstract core language that integrates key concepts needed to describe a service. Parts of the core language can be substituted with concrete DSLs. Thus, the framework serves as a basis for the comprehensive specification and automatic matching of services.

Model-driven specification of adaptive cloud-based systems - Nagel, Benjamin; Gerth, Christian; Yigitbas, Enes; Christ, Fabian; Engels, Gregor (Proceedings of the 1st International Workshop on Model-Driven Engineering for High Performance and CLoud computing co-located with 15th International Conference on Model Driven Engineering Languages and Systems {(MODELS} 2012), Innsbruck, Austria, October 01 - 05, 2012)

Entwicklung eines Monitoring- und Adaptionskonzeptes für Geschäftsprozesse in service-orientierten Systemen - Yigitbas, Enes

Coverage Criteria for Testing DMM Specifications - Arifulina, Svetlana; Engels, Gregor; Soltenborn, Christian (Proceedings of the 11th International Workshop on Graph Transformation and Visual Modeling Techniques (GT-VMT))
Behavioral modeling languages are most useful if their behavior is specified formally such that it can e.g. be analyzed and executed automatically. Obviously, the quality of such behavior specifications is crucial. The rule-based semantics specification technique Dynamic Meta Modeling (DMM) honors this by using the approach of Test-driven Semantics Specification (TDSS), which makes sure that the specification at hand at least describes the correct behavior for a suite of test models. However, in its current state TDSS does not provide any means to measure the quality of such a test suite. In this paper, we describe how we have applied the idea of test coverage to TDSS. Similar to common approaches of defining test coverage criteria, we describe a data structure called invocation graph containing possible orders of applications ofDMM rules. Then we define different coverage criteria based on that data structure, taking the rule applications caused by the test suite’s models into account. Our implementation of the described approach gives the language engineer using DMM a means to reason about the quality of the language’s test suite, and also provides hints on how to improve that quality by adding dedicated test models to the test suite.

Multi-Modal, Multi-Touch Interaction with Maps in Disaster Management Applications - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (ISPRS - International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)

Designing Multi-Modal Map-Based Interfaces for Disaster Management - Paelke, Volker; Nebe, Karsten; Geiger, Christian; Klompmaker, Florian; Fischer, Holger Gerhard (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Authenticated Tangible Interaction using RFID and Depth-Sensing Cameras - Supporting Collaboration on Interactive Tabletops - Klompmaker, Florian; Fischer, Holger Gerhard; Jung, Helge (Proceedings of the 5th International Conference on Advances in Computer-Human Interaction (ACHI))

Integrating usability engineering in the software development lifecycle based on international standards - Fischer, Holger Gerhard (Proceedings of the 4th ACM SIGCHI symposium on Engineering interactive computing systems - EICS '12)

Enriching Disaster Control Management based on Human-Computer Design - Fischer, Holger Gerhard; Klompmaker, Florian (Proceedings of the 9th International Conference on Information Systems for Crisis Response and Management (ISCRAM))

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Geis, Thomas; Kluge, Oliver; Bogner, Christian; Polkehn, Knut (Jahresband Usability Professionals)

German UPA Qualitätsstandard für Usability Engineering - Behrenbruch, Kay; Bogner, Christian; Fischer, Holger Gerhard; Geis, Thomas; Geitner, Claudia; Heimgärtner, Rüdiger; Hofmann, Britta; Hunkirchen, Peter; Kluge, Oliver; Litzenberg, Britta; Molich, Rolf; Polkehn, Knut; et al.

A UML-based Rich Service Description for Automatic Service Discovery - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)
Service-oriented computing (SOC) emerges as a promising trend solving many issues in distributed software development. Following the essence of SOC, service descriptions are dened by the service partners based on current standards, e.g., WSDL [15]. However, these standards are mostly structural and do not provide any behavioral description, which may lead to inaccurate service discovery results. There is a requirement for a rich service description language for service partners that encompasses the structural as well as behavioral information in the service description. Furthermore, service discovery based on an automatic matching of these comprehensive service descriptions is a complex task, which is further complicated through the heterogeneity of the service partners' domains in terms of dierent underlying ontologies. In this paper, we propose a rich service description language based on UML, which allows the specication of structural and behavioral features of a service. In addition, we also briefly discuss how some existing matching approaches can be extended to dene an automatic matching mechanism for rich service descriptions resolving the underlying heterogeneity.

IT ist nicht gleich IT: Ein Plädoyer für eine situationsbezogene Softwareentwicklung - Dumslaff, Uwe; Engels, Gregor; Kremer, Marion (OBJEKTspektrum)

Systematic evolution of model-based spreadsheet applications - Luckey, Markus; Erwig, Martin; Engels, Gregor (Journal of Visual Languages & Computing)

Generalized Kripke semantics for the Lambek-Grishin calculus - Chernilovskaya, Anna; Gehrke, Mai; van Rooijen, Lorijn (Logic Journal of IGPL)

Sichern der Zukunftsfähigkeit bei der Migration von Legacy-Systemen durch modellgetriebene Softwareentwicklung - Grieger, Marvin; Güldali, Baris; Sauer, Stefan (Softwaretechnik-Trends, Proceedings of the 14th Workshop Software-Reengineering (WSR))

Ten years of software and systems modeling - Engels, Gregor; Whittle, Jon (Software & Systems Modeling)

Semantisches Content Management - Christ, Fabian; Nagel, Benjamin; Bachman-Gmür, Reto; Westenthaler, Rupert (JavaMagazin)

Agiles Testen in Scrum – Testtypen und Abläufe - Geisen, Silke; Güldali, Baris (OBJEKTspektrum (Online Themenspecials))
Mittlerweile sind viele Unternehmen dazu übergegangen, ihre Software „agil“ zu entwickeln. Die damit verbundenen Erwartungen sind vor allem ein frühes Kundenfeedback sowie eine kürzere „Time-to-Market“ durch entsprechend schnelle Release-Zyklen. Hinter den Kulissen finden sich jedoch oftmals Probleme, sodass die erwarteten Vorteile agiler Softwareentwicklung nicht oder nur teilweise zum Tragen kommen. Gründe dafür liegen selten an technischen Hürden, sondern oftmals in einer zu oberflächlichen Interpretation der Philosophie von agiler Softwareentwicklung und den damit zusammenhängenden Kernzielen: Planung und Analyse auf ein sinnvolles Maß zu reduzieren und zugleich unnötige Arbeiten zu vermeiden. Was sinnvoll und was unnötig ist, stellt dabei eine der wesentlichen Herausforderungen dar.

Quasar 3.0 - A Situational Approach to Software Engineering - Kremer, Marion; Engels, Gregor; Hofmann, Alexander; Hohwiller, Jörg; E. Nandico, Oliver; Nötzold, Thomas; Prott, Karl; Schlegel, Diethelm; Seidl, Andreas; Wolf, Thomas

Model-Based Testing: Achievements and Future Challenges - Mlynarski, Michael; Güldali, Baris; Weißleder, Stephan; Engels, Gregor (Advances in Computers)
Software systems are part of our everyday life and they become more complex day by day. The ever-growing complexity of software and high quality requirements pose tough challenges to quality assurance. The quality of a software system can be measured by software testing. However, if manually done, testing is a time-consuming and error-prone task. Especially test case design and test execution are the most cost-intensive activities in testing. In the previous 20 years, many automation tools have been introduced for automating test execution by using test scripts. However, the effort for creating and maintaining test scripts remains. Model-based testing (MBT) aims at improving this part by systematizing and automating the test case design. Thereby, test cases or automatable test scripts can be generated systematically from test models. MBT is already known for several years, but it currently gains a great momentum due to advanced tool support and innovative methodological approaches. This chapter aims at giving an overview of MBT and summarizes recent achievements in MBT. Experiences with using the MBT approach are illustrated by reporting on some success stories. Finally, open issues and future research challenges are discussed.

Automatische Kompatibilitätsprüfung Framework-basierter Anwendungen - Christ, Fabian
Software-Architekturen betrieblicher Informationssysteme bestehen aus Architekturbausteinen wie Frameworks, Komponenten und Bibliotheken. Die Entwicklung dieser Architekturen unter Einbeziehung wiederverwendbarer Architekturbausteine ist eine Voraussetzung einer industriell organisierten Software-Entwicklung. Für eine effiziente Trennung der Zuständigkeiten werden dabei häufig Architekturbausteine von Drittanbietern wiederverwendet.Frameworks als erweiterbare Architekturbausteine bieten besondere Vorteile. Sie erlauben sowohl die Wiederverwendung der Funktionalität als auch der durch das Framework vorgegebenen Software-Architektur. Beispiele sind Frameworks für Benutzungsoberflächen oder für die Anbindung von Datenbanken. Durch Implementierung anwendungsspezifischer Erweiterungen wird ein Framework für den konkreten Anwendungsfall angepasst. Eine Anwendung, deren Software-Architektur ein Framework einsetzt, benutzt das Framework über dessen Erweiterungspunkte.Im Laufe der Evolution einer solchen Anwendung entsteht häufig die Situation, dass das Framework durch eine neuere Version aktualisiert werden soll. Die Aktualisierung enthält das Risiko, dass Inkompatibilitäten zwischen bestehender Anwendung und neuer Framework-Version auftreten, die wiederum zu aufwendigen Anpassungen führen. Daher müssen mögliche Inkompatibilitäten vor der Aktualisierung erkannt und bewertet werden. Nach aktuellem Stand der Technik ist dies nicht möglich, so dass es in der industriellen Praxis zu unvorhergesehenen Problemen verbunden mit hohen Kosten kommt.Wir stellen ein Verfahren zur automatischen Kompatibilitätsanalyse Framework-basierter Anwendungen vor, mit dem das beschriebene Problem gelöst wird. Durch eine Kombination aus Codeanalyse und neuartiger Framework-Beschreibung lassen sich mögliche Inkompatibilitäten vor Durchführung der Aktualisierung automatisch berechnen. Eine prototypische Implementierung des Verfahrens im Werkzeug »Companian« demonstriert die praktische Einsetzbarkeit unseres Verfahrens.Für die Definition der benötigten Framework-Beschreibungssprache mittels Meta-Modellierung setzen wir die neuartige Modellierungstechnik der parametrisierten Meta-Modelle ein. Die Technik unterstützt unseren Ansatz einer anforderungsbasierten Wiederverwendung von Sprachen. Mit diesem Ansatz können bestehende Sprachen für Teilaspekte neu definierter Sprachen wiederverwendet werden. Unser pragmatischer Ansatz stellt dabei sicher, dass hierbei nur die Sprachen benutzt werden können, die syntaktisch und semantisch den geforderten Sprachen entsprechen.

Towards Rich Change Management for Business Process Models - Gerth, Christian; Luckey, Markus (Proceedings of the Workshop on Comparison and Versioning of Software Models (CVSM'12))

A UML-based Rich Service Description Language for Automatic Service Discovery of Heterogeneous Service Partners - Huma , Zille; Gerth , Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the Forum at the CAiSE'12 Conference on Advanced Information Systems Engineering)

Modeling with Adapt Cases - Luckey , Markus; Mutz, Felix (Repository for Model-Driven Development (ReMoDD))

Ein Ansatz zur dynamischen Qualitätsmessung, -bewertung und Anpassung von Software Engineering Methoden - Geisen , Silke; Luckey , Markus; Engels, Gregor (Proceedings of 19. GI-WIVM Workshop: Qualitätsmanagement und Vorgehensmodelle)

Towards a Framework for the Integration of Modeling Languages - Arifulina, Svetlana (Proceedings of the Doctoral Symposium of the 5th International Conference on Software Language Engineering 2012, Dresden, Germany (SLE (Doctoral Symposium)))

Entwicklung eines Softwarewerkzeugs für die modellgetriebene Migration betrieblicher Informationssysteme - Güldali , Baris; Sauer, Stefan; Löhr, Perdita (Proceedings of the Workshop Modellbasierte und Modellgetriebene Softwaremodernisierung (MMSM 2012))

Assessing composition in modeling approaches - Mussbacher , Gunter; Alam , Omar; Alhaj , Mohammed; Ali , Shaukat; Amálio , Nuno; Barn , Balbir; Bræk , Rolv; Clark , Tony; Combemale , Benoit; Cysneiros , Luiz Marcio; Fatima , Urooj; France , Robert; et al. (Proceedings of the Workshop about Comparing Modeling Approaches 2012 (@MODELS 2012))

Multi-Staged Quality Assurance for Self-Adaptive Systems - Luckey , Markus; Thanos , Christian; Gerth, Christian; Engels, Gregor (Proceedings of 1st International Workshop on EVALUATION for SELF-ADAPTIVE and SELF-ORGANIZING SYSTEMS at SASO'12)

Ein Ansatz zur Anpassung von Software Engineering Methoden im laufenden Projekt - Geisen, Silke (Proceedings of Software Engineering 2012 (SE 2012) - Doktorandensymposium)

Optimized XPath evaluation for Schema-compressed XML data - Böttcher, Stefan; Hartel, Rita; Heindorf, Stefan (ADC)

Generalizing and Improving SQL/XML Query Evaluation - Böttcher, Stefan; Bokermann, Dennis; Hartel, Rita (8th International Conference on Signal Image Technology and Internet Based Systems (SITIS'12))

Kompatibilitätsanalyse bei Evolution framework-basierter Anwendungen - Christ, Fabian; Bals, Jan-Christopher (Proceedings of the 3rd Design for Future Workshop held at the Software Engineering 2011 Conference (SE2011), Karlsruhe (Germany))

A Reference Architecture for Semantic Content Management Systems - Christ, Fabian; Nagel, Benjamin (Proceeding of the Enterprise Modelling and Information Systems Architectures Workshop 2011 (EMISA'11), Hamburg (Germany))

Situational Software Engineering: Ein Rahmenwerk für eine situationsgerechte Auswahl von Entwicklungsmethoden und Vorgehensmodellen - Engels, Gregor; Kremer, Marion (Proceedings der41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011;)

Services aus der Cloud = Fahren im Nebel? Wie minimiere ich die Risiken und erreiche hohe Qualität? - Engels, Gregor (Proceedings der 41. Jahrestagung der Gesellschaft für Informatik - Informatik 2011)
Der Kostendruck einerseits und die Verfügbarkeit des Internets andererseits führen dazu, dass Softwaresysteme auf Services aus der Cloud zurückgreifen (müssen bzw. können). Dies gilt für alle Anwendungsbereiche und somit insbesondere auch für die Software im Auto. Aber wie sorge ich dafür, dass die Services aus der Cloud zu meinem Softwaresystem passen und die Anforderungen erfüllen? Der Vortrag diskutiert aktuelle Ansätze der konstruktiven und analytischen Qualitätssicherung, um durch Maßnahmen sowohl zur Entwicklungs- als auch Laufzeit eine hohe Qualität beim Einsatz von Services aus der Cloud zu erzielen. Insbesondere wird über aktuelle Arbeiten im neuen DFG Sonderforschungsbereich 901 "On-the-Fly Computing" berichtet.

Precise Mappings between Business Process Models in Versioning Scenarios - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 8th International Conference on Services Computing (SCC'11))

Selektionswerkzeug zur Auswahl projektspezifischer Vorgehensstrategien - Heinemann, Marianne; Palme, Markus; Rothmann, Andreas; Salger, Frank; Schönke, Jürgen; Engels, Gregor (Software Engineering 2011)

Pattern-Based Modeling and Formalizing of Business Process Quality Constraints - Khaluf, Lial; Gerth, Christian; Engels, Gregor (Proceedings of the 23rd International Conference on Advanced Information System Engineering (CAiSE'11))
The quality of business processes can be checked by verifying their compliance with specific quality constraints. These constraints represent a set of required temporal and logical relationships between different steps of business processes. Quality constraints are usually formulated as informal texts, which makes them difficult to be verified, when business processes become complex. One way to solve this problem is by automating the verification of quality constraints on business processes by applying model checking. To apply model checking, both business processes and quality constraints have to be formalized. In this paper, we define a new visual language for modeling quality constraints and we provide a pattern-based translation for quality constraint models into Computation Tree Logic formulas.

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Adapt Cases: Extending Use Cases for Adaptive Systems - Luckey, Markus; Nagel, Benjamin; Gerth, Christian; Engels, Gregor (Proceeding of the 6th international symposium on Software engineering for adaptive and self-managing systems)

QUAASY - QUality Assurance of Adaptive SYstems - Luckey, Markus; Gerth, Christian; Soltenborn, Christian; Engels, Gregor (Proceedings of the 8th International Conference on Autonomic Computing (ICAC'11))

Extending DMM Behavior Specifications for Visual Execution and Debugging - Bandener, Nils; Soltenborn, Christian; Engels, Gregor (Proceedings of the 3rd International Conference on Software Language Engineering (SLE 2010))

Testen von Software-Produktlinien - Brüseke, Frank; Christ, Fabian; Sauer, Stefan; Wübbeke, Andreas

Exploiting New Interaction Techniques for Disaster Control Management Using Multitouch-, Tangible- and Pen-Based-Interaction - Nebe, Karsten; Klompmaker, Florian; Jung, Helge; Fischer, Holger Gerhard (Human-Computer Interaction. Interaction Techniques and Environments.)

Multitouch-, Be-Greifbare- und Stiftbasierte-Interaktion in der Einsatzlageplanung - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian (Human Centered Design)

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk (Jahresband Usability Professionals)

Modellbasiertes Testen: Hype oder Realität? - Weißleder, Stephan; Güldali, Baris; Mlynarski, Michael; Törsel, Arne-Michael; Faragó, David; Prester, Florian; Winter, Mario (OBJEKTspektrum)
Manuelle Testerstellung verursacht hohe Kosten. Im Vergleich dazu bietet modellbasiertes Testen große Vorteile hinsichtlich Testautomatisierung, früher Fehlerfindung, Erhöhung der Testabdeckung, effizienten Testentwurfs und besserer Rückverfolgbarkeit. Die Einführung des modellbasierten Testens ist jedoch mit Investitionen verbunden, für die die Rendite häufig unklar erscheint. Dabei finden sich in der Literatur bereits etliche Erfahrungsberichte zur erfolgreichen Einführung von modellbasiertem Testen in unterschiedlichen Anwendungsdomänen. In diesem Artikel präsentieren wir einen Überblick über einige dieser Erfahrungsberichte.

TORC: test plan optimization by requirements clustering - Güldali, Baris; Funke, Holger; Sauer, Stefan; Engels, Gregor (Software Quality Journal)
Acceptance testing is a time-consuming task for complex software systems that have to fulfill a large number of requirements. To reduce this effort, we have developed a widely automated method for deriving test plans from requirements that are expressed in natural language. It consists of three stages: annotation, clustering, and test plan specification. The general idea is to exploit redundancies and implicit relationships in requirements specifications. Multi-viewpoint techniques based on RM-ODP (Reference Model for Open Distributed Processing) are employed for specifying the requirements. We then use linguistic analysis techniques, requirements clustering algorithms, and pattern-based requirements collection to reduce the total effort of testing against the requirements specification. In particular, we use linguistic analysis for extracting and annotating the actor, process and object of a requirements statement. During clustering, a similarity function is computed as a measure for the overlap of requirements. In the test plan specification stage, our approach provides capabilities for semi-automatically deriving test plans and acceptance criteria from the clustered informal textual requirements. Two patterns are applied to compute a suitable order of test activities. The generated test plans consist of a sequence of test steps and asserts that are executed or checked in the given order. We also present the supporting prototype tool TORC, which is available open source. For the evaluation of the approach, we have conducted a case study in the field of acceptance testing of a national electronic identification system. In summary, we report on lessons learned how linguistic analysis and clustering techniques can help testers in understanding the relations between requirements and for improving test planning.

Using rule overriding to improve reusability and understandability of Dynamic Meta Modeling specifications - Soltenborn, Christian; Engels, Gregor (Journal of Visual Languages & Computing)
Dynamic Meta Modeling (DMM) is a visual semantics specification technique targeted at languages based on a metamodel. A DMM specification consists of a runtime metamodel and operational rules which describe how instances of the runtime metamodel change over time. A known deficiency of the DMM approach is that it does not support the refinement of a DMM specification, e.g., in the case of defining the semantics for a refined and extended domain-specific language (DSL). Up to now, DMM specifications could only be reused by adding or removing DMM rules. In this paper, we enhance DMM such that DMM rules can override other DMM rules, similar to a method being overridden in a subclass, and we show how rule overriding can be realized with the graph transformation tool GROOVE. We argue that rule overriding does not only have positive impact on reusability, but also improves the intuitive understandability of DMM semantics specifications.

Physiologische Beanspruchungsreaktionen bei der Anwendung von kopfgetragenen AR-Displays - Böckelmann, Irina; Schenk, Daniel; Rößler, Thoralf; Adler, Simon; Senft, Björn; Grubert, Jens; Mecke, Rüdiger; Huckauf, Anke; Urbina, Mario; Tümler, Johannes; Darius, Sabine

User Centered Design Process of OSAMi-D - Developing User Interfaces for a Remote Ergometer Training Application - Klompmaker, Florian; Senft, Björn; Nebe, Karsten; Busch, Clemens; Willemsen, Detlev (HEALTHINF 2011 - Proceedings of the International Conference on Health Informatics, Rome, Italy, 26-29 January, 2011)

Palladio-based performance blame analysis - Brüseke, Frank; Becker, Steffen; Engels, Gregor (Proceedings of the 16th International Workshop on Component-Oriented Programming (WCOP; satellite event of the CompArch 2011), Boulder Colorado, CO (USA))
Performance is an important quality attribute for business information systems. When a tester has spotted a performance error, the error is passed to the software developers to fix it. However, in component-based software development the tester has to do blame analysis first, i. e. the tester has to decide, which party is responsible to fix the error. If the error is a design or deployment issue, it can be assigned to the software architect or the system deployer. If the error is specific to a component, it needs to be assigned to the corresponding component developer. An accurate blame analysis is important, because wrong assignments of errors will cause a loss of time and money. Our approach aims at doing blame analysis for performance errors by comparing performance metrics obtained in performance testing and performance prediction. We use performance prediction values as expected values for individual components. For performance prediction we use the Palladio approach. By this means, our approach evaluates each component’s performance in a certain test case. If the component performs poorly, its component developer needs to fix the component or the architect replaces the component with a faster one. If no omponent performs poorly, we can deduce that there is a design or deployment issue and the architecture needs to be changed. In this paper, we present an exemplary blame analysis based on a web shop system. The example shows the feasibility of our approach.

Semi-automatische Ableitung externer Anpassungsmechanismen für selbst-adaptive Systeme - Nagel, Benjamin (Proceedings of the Software Engineering 2011 (SE 2011), Karlsruhe (Germany))

Precise Mappings between Business Process Models in Versioning Scenarios - Gerth, Christian; Luckey, Markus; Küster, Jochen; Engels, Gregor (Proceedings of the IEEE 8th International Conference on Service Computingt (SCC))
In the development process of service-oriented systems, business process models are used at different levels. Typically, high-level business process models that describe business requirements and needs are stepwise refined to the IT level by different business modelers and software architects. As a result, different process model versions must be compared and merged by means of model version control. An important prerequisite for process model version control is an elaborated matching approach that results in precise mappings between different process model versions. The challenge of such an approach is to deal with syntactically different process models that are semantically equivalent. For that purpose, matching techniques must consider the semantics of process modeling languages.In this paper, we present a matching approach for process models in a versioning scenario. Based on a term formalization of process models, we enable an efficient and effective way to match syntactically different but semantically equivalent process models resulting in precise mappings.

Coverage Criteria for Testing DMM Specifications - Arifulina, Svetlana

Computing Compressed XML Data from Relational Databases - Böttcher, Stefan; Bokermann, Dennis; Hartel, Rita (Advances in Databases - 28th British National Conference on Databases, BNCOD 28, Revised Selected Papers)

Graph Transformations and Model-Driven Engineering - Essays Dedicated to Manfred Nagl on the Occasion of his 65th Birthday